A review of sulfate-reducing bacteria: Metabolism, influencing factors and application in wastewater treatment. (20th November 2022) - Zhang, Zhao; Zhang, Chunhui; Yang, Yang; Zhang, Zhuowei; Tang, Yuanhui; Su, Peidong; Lin, Zhiwei
Abstract: With the rapid economy and population growth, wastewater containing sulfate originated from industrial and human activities have gradually become a potential threat to the ecological security. As dominant microorganism responsible for treating high-sulfate wastewater, the sulfate-reducing bacteria (SRB) not only utilizes sulfate as the terminal electron acceptors, but also resists various harsh environments, so it was applied to a broader range of wastewater treatment. Based on previous studies, this study provides a comprehensive review of the metabolic mechanism and functional organisms of SRB. Further, the influence mechanism of environmental factors on the metabolic activity of SRB was analyzed from the perspective of pH, temperature, COD/SO4 2− ratio, electron donors, oxidation reduction potential, hydraulic retention time, concomitant ions, and syntrophic/competitive effect. Additionally, applications and enhancing strategies for SRB were discussed based on above mechanism of action. Lastly, existing challenges and future development directions in environmental engineering applications are proposed. Future analysis should focus on functional genes and enzymes in assimilation sulfate reduction, research of SRB with complete oxidation capacity, the establishment of mathematical models simulating the metabolic activity and efficiency of SRB, the development of novel carbon sources fit for SRB, the potential value of heavy metals and S0 recovery in sulfate reduction, and exploration of interaction mechanism between organohalides-respiring bacteria (OHRB) and SRB. Graphical abstract: Image 1 Highlights: The metabolic mechanism of SRB were summarized through metabolic pathways, functional organisms and key genes. Eight key influencing factors affecting the metabolic activity of SRB were summarized. SRB-mediated wastewater treatment technology is crucial in the process of water pollution control. Further challenges and directions for SRB applications in environmental engineering are presented.